2015
DOI: 10.1038/npjschz.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Biological pathways modulated by antipsychotics in the blood plasma of schizophrenia patients and their association to a clinical response

Abstract: Proteomics is a valuable tool to unravel molecular mechanisms involved in human disorders. Considering the mediocre effectiveness of antipsychotics, which are the main class of drug used to treat schizophrenia, we analyzed a cohort of 58 schizophrenia patients who had blood collected before and after 6 weeks of antipsychotic treatment using a shotgun mass spectrometry proteomic profiling approach. Our aim was to unravel molecular pathways involved with an effective drug response. The results showed that all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…The samples had already been obtained from a cohort comprised of 54 acute schizophrenia patients who were treated with either olanzapine ( n = 17), risperidone ( n = 23), or quetiapine ( n = 14) (Supplementary Table 1 ), as described previously ( 15 ). Diagnoses were performed using DSM-IV criteria and the Structured Clinical Interview (SCID-I) ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples had already been obtained from a cohort comprised of 54 acute schizophrenia patients who were treated with either olanzapine ( n = 17), risperidone ( n = 23), or quetiapine ( n = 14) (Supplementary Table 1 ), as described previously ( 15 ). Diagnoses were performed using DSM-IV criteria and the Structured Clinical Interview (SCID-I) ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is critical since different patients may show a better response to a distinct drug. In a recent publication, we reported on the analysis of plasma samples from a cohort of 58 schizophrenia patients using shotgun mass spectrometry proteomic profiling ( 15 ). Our objective was to identify proteins and protein pathways involved with an effective response to atypical antipsychotics, although, as with the above studies, no attempt was made to identify treatment-specific signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Gil-Pisa, et al justified the use of their mouse model of schizophrenia based on its similarity in cytokine expression to a previously published model [10]. Martins-de-Souza, et al showed that responders showed the same pathways were affected, but in opposite directions, in poor vs. good responders to anti-psychotics [11]. Clearly, this idea has many potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Gil-Pisa, et al justified the use of their mouse model of schizophrenia based on its similarity in cytokine expression to a previously published model (Gil-Pisa et al 2014). Martins-de-Souza, et al showed that responders showed the same pathways were affected, but in opposite directions, in poor vs. good responders to anti-psychotics (Martins-de-Souza et al 2015). Clearly, this idea has many potential applications.…”
Section: Introductionmentioning
confidence: 99%